Quality Education in the Digital Age: Adapting to 21st Century Primary School Learners - Blyznyuk, Oleksandr; Kachak, Tetiana; Blyznyuk, Tetyana; Katarzyna Nazaruk, Stanisława (Journal of Vasyl Stefanyk Precarpathian National University, 2025)
A concise summary of the article, highlighting the problem, methodology, key findings, and implications for education in the digital age. The rapid advancements in digital technology have significantly transformed education, presenting both opportunities and challenges for primary school learners in the 21st century. This article explores the concept of quality education in the digital age, emphasizing the need to adapt teaching practices and methodologies to meet the evolving needs of digital-native students. It examines the unique characteristics of 21st-century learners, including their reliance on technology, preference for interactive and personalized learning experiences, and ability to process information from multiple sources simultaneously. The study reviews existing literature on digital tools and techniques applied in primary education, highlighting global trends, innovative practices, and the benefits of technology in enhancing student engagement and learning outcomes. Additionally, it addresses challenges such as the digital divide, disparities in access to technology, and the need for teacher training and curriculum redesign to effectively integrate digital tools. Through a comprehensive analysis, this article identifies key strategies for adapting primary education to the digital age. These include fostering digital literacy, leveraging gamification and adaptive learning platforms, promoting collaborative online learning environments, and ensuring equitable access to digital resources. The findings underscore the importance of a holistic approach that combines technology with pedagogical innovation to create meaningful, inclusive, and future-ready learning experiences for primary school students. The article concludes with practical recommendations for educators, policymakers, and researchers to advance quality education in the digital age while addressing emerging challenges and opportunities.